2001
DOI: 10.1074/jbc.m006184200
|View full text |Cite
|
Sign up to set email alerts
|

The Single Pore Residue Asp542 Determines Ca2+ Permeation and Mg2+ Block of the Epithelial Ca2+ Channel

Abstract: The epithelial Ca 2؉ channel (ECaC), which was recently cloned from rabbit kidney, exhibits distinctive properties that support a facilitating role in transcellular Ca 2؉ (re)absorption. ECaC is structurally related to the family of six transmembrane-spanning ion channels with a pore-forming region between S5 and S6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(139 citation statements)
references
References 15 publications
3
136
0
Order By: Relevance
“…CNG and TRP channels both contain a pore forming P-loop between S5 and S6, which includes a selectivity filter and is typical for various cation channels (40). In TRP channels, mutations in this region may alter the ratio of monovalent over divalent cation permeability (25,26,28). In CNG channels, even the cation versus anion selectivity can be reverted by mutations of this region.…”
Section: Discussionmentioning
confidence: 99%
“…CNG and TRP channels both contain a pore forming P-loop between S5 and S6, which includes a selectivity filter and is typical for various cation channels (40). In TRP channels, mutations in this region may alter the ratio of monovalent over divalent cation permeability (25,26,28). In CNG channels, even the cation versus anion selectivity can be reverted by mutations of this region.…”
Section: Discussionmentioning
confidence: 99%
“…However, the only negatively charged amino acid residues in the putative pore-forming region of TRPV6 are a glutamate residue at position 535 and two aspartate residues at positions 542 and 550. All three amino acids are conserved in the TRPV5 protein from rabbit and especially the aspartate residue at position 542 has been shown to decisively affect Ca 2ϩ permeation (27,28). Substituting aspartate at position 542 versus an alanine in human TRPV6 abolished channel activity (10), which was also the case if this pore mutant was C-terminally EGFP-tagged.…”
Section: Discussionmentioning
confidence: 99%
“…All of the nonpolar amino acids were replaced by a polar amino acid, Ser, and the polar amino acids were replaced by a small, nonpolar 1 The abbreviations used are: GFP, green fluorescence protein; GST, glutathione S-transferase. amino acid, Ala. Gly is classified as a polar amino acid and was thus replaced by Ala. Because it has been reported that the negatively charged amino acids Glu and Asp in the transmembrane domain contribute to ion selectivity in voltage-gated Ca 2ϩ channels (30,31) and ECaC (32,33) and to interaction with channel blockers (34,35), the remarkable Asp 341 was replaced by each of 7 amino acids, Glu, Lys, Arg, Thr, Asn, Ala, and Leu, and the positively charged amino acid His 353 was also replaced by each of 3 amino acids, Asp, Arg, and Ala. The mutant genes bearing these single amino acid substitutions were then introduced into cells of the mid1-⌬5 mutant, and the resulting transformants were examined for viability and Ca 2ϩ accumulation after exposure to ␣-factor.…”
Section: H3 Is Essential For Mid1mentioning
confidence: 99%